POLA ASUH PETANI KELAPA SAWIT DALAM MENDIDIK ANAK DI DUSUN REJO SARI, KEPENGHULUAN BANGKO SEMPURNA, BANGKO PUSAKO, ROKAN HILIR - Marina Marina; Daeng Ayub; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the type of dominant parenting practices applied by Palm Oil Farmers in Educating Children in Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hilir. Which in terms of authoritarian parenting, permissive parenting, and authoritarian/ democratic parenting. In addition, this study also aims to determine the contribution of each indicator to the variables of Palm Oil Farmer Parenting in Educating Children in Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hilir. The problem formulation of this research is what type of parenting is dominantly applied by Palm Oil Farmers in Educating Their Children in Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hilir? How big is the contribution of the indicator to the variables of parenting of oil palm farmers in educating their children in Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hilir? This research consists of 3 indicators, in accordance with the opinion of Syamsul Kurniawan. The sample of this study used the Simple Random Sampling technique, because the sampling of members of the population was carried out randomly without regard to strata in the population. How to do this if the population members are considered homogeneous, (Sugiyono, 2011: 57). Data collection techniques, documentation, observation, interviews and questionnaires, totaling 56 statements. Data obtained from respondents totaling 20 people for the trial sample and 78 people for the study sample. After the questionnaire was tested, there were 4 statements and the researcher discarded invalid statements. Based on the average value of the mean for the Palm Oil Farmer Parenting Pattern in Educating Children in Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hillir are classified as high with a mean value of 4.46 and SD 0.17. The interpretation obtained for each indicator of Palm Oil Farmer Parenting in Educating Children in the Dusun Rejo Sari, Kepenghuluan Bangko Sempurna, Bangko Pusako, Rokan Hilir may be classified as high. So, seen the most dominant of these 3 indicators is democratic parenting. Key Words: Parenting, Oil Palm Farmers, Educating Children